Saturable Absorption Measurement of Platinum as Saturable Absorber by using Twin Detector Method Based on Mode-Locked Fiber Laser - Azmi, Atiqah Nabieha; Awang, Noor Azura; Zakaria, Zahariah; Abdul Hadi, Fatin Shaqira; Yuzaile, Yushazlina Roshaini (Journal of Science and Technology, 2017)
:Â  This paper illustrates the absorption measurement of Pt as saturable absorber (SA) by using mode-locked fiber laser system. The SA is fabricated by depositing 10 nm of Pt on the fiber ferrules using sputtering method. The absorption measurement of Pt is characterised by employing a balanced twin detector method based on mode-locked fiber laser with central wavelength of 1532.25 nm, repetition rate of 2.833 MHz and pulse duration of 34.3 ns. The Pt-SA produce modulation depth of 21.9% and saturation intensity of 21.6 MW cm-2.